2017
DOI: 10.1242/dev.143727
|View full text |Cite
|
Sign up to set email alerts
|

Escort cells generate a dynamic compartment for germline stem cell differentiation via combined Stat and Erk signalling

Abstract: Two different compartments support germline stem cell (GSC) selfrenewal and their timely differentiation: the classical niche provides maintenance cues, while a differentiation compartment, formed by somatic escort cells (ECs), is required for proper GSC differentiation. ECs extend long protrusions that invade between tightly packed germ cells, and alternate between encapsulating and releasing them. How ECs achieve this dynamic balance has not been resolved. By combining live imaging and genetic analyses in Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 57 publications
8
52
0
Order By: Relevance
“…Multiple somatic cell types are significantly enriched for genes expressing proteins with roles in mediating cell-cell communication. These protein classes will expand previous observations which showed that, in addition to conventional signaling pathways, ovarian cells coordinate their behaviors through alternative modes of signaling (Banisch et al, 2017;Gilboa et al, 2003). For example, a gap junction protein zpg is highly enriched in germ cells, while other gap junction proteins, inx2, inx3, and ogre, are expressed in somatic cell types surrounding the germ cells.…”
Section: Cell Type Specific Transcriptional Signatures Reveal Functiosupporting
confidence: 51%
See 1 more Smart Citation
“…Multiple somatic cell types are significantly enriched for genes expressing proteins with roles in mediating cell-cell communication. These protein classes will expand previous observations which showed that, in addition to conventional signaling pathways, ovarian cells coordinate their behaviors through alternative modes of signaling (Banisch et al, 2017;Gilboa et al, 2003). For example, a gap junction protein zpg is highly enriched in germ cells, while other gap junction proteins, inx2, inx3, and ogre, are expressed in somatic cell types surrounding the germ cells.…”
Section: Cell Type Specific Transcriptional Signatures Reveal Functiosupporting
confidence: 51%
“…In addition to common developmental origins, an overlap in transcriptional signatures may also reflect shared functions. Consistently, ICs and FCs both intimately interact with germ cells and guide their differentiation (Banisch et al, 2017;Wu et al, 2008;Xie, 2013)…”
Section: Discussionmentioning
confidence: 99%
“…A second signaling center, sometimes termed a "differentiation niche, " is formed by the somatic escort cells (also called inner germarial sheath cells) ( Figure 2D). Escort cells promote germ cell differentiation and guide the posterior movement of differentiated cysts (Decotto and Spradling, 2005;Morris and Spradling, 2011;Banisch et al, 2017). Escort cells line the outside of the anterior germarium (regions 1-2) and send long, thin cellular protrusions into the center of the germarium, around the dividing germ cells (Kirilly et al, 2011;Morris and Spradling, 2011;Banisch et al, 2017).…”
Section: Paracrine Signaling Promotes Gsc Self-renewal and Daughter Cmentioning
confidence: 99%
“…Escort cells promote germ cell differentiation and guide the posterior movement of differentiated cysts (Decotto and Spradling, 2005;Morris and Spradling, 2011;Banisch et al, 2017). Escort cells line the outside of the anterior germarium (regions 1-2) and send long, thin cellular protrusions into the center of the germarium, around the dividing germ cells (Kirilly et al, 2011;Morris and Spradling, 2011;Banisch et al, 2017). Escort cell protrusions dynamically wrap the dividing cystoblasts and are essential for mitotic division of the cysts, as well as the association of follicle cells with the germline at encapsulation.…”
Section: Paracrine Signaling Promotes Gsc Self-renewal and Daughter Cmentioning
confidence: 99%
“…Normal Wnt pathway activity is among those shown to be important for this function in ECs and pre-ECs (Hamada-Kawaguchi et al, 2014;Luo et al, 2015;Mottier-Pavie et al, 2016;Upadhyay et al, 2018;Waghmare and Page-McCaw, 2018;Wang et al, 2015;Wang and Page-McCaw, 2018). It is not known what drives ordered posterior movement of germline cysts in adult germaria but this also may depend on EC interactions (Banisch et al, 2017). In future it will be interesting to investigate whether pupal or adult ECs have graded EC adhesive properties or send graded differentiation signals according to their AP position, instructed for example by the strength of Wnt signaling.…”
Section: Coordination Between Germline and Somatic Ovarian Cell Develmentioning
confidence: 99%